2019
DOI: 10.4012/dmj.2018-173
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial potential of bismuth lipophilic nanoparticles embedded into chitosan-based membrane

Abstract: The objective of this work was to analyze the antimicrobial and antibiofilm activities of bismuth lipophilic nanoparticles (BisBAL NPs) incorporated into chitosan-based membranes. Chitosan-based membranes were homogeneously embedded with BisBAL NPs, confirming the bismuth presence by scanning electron microscopy. The tensile strength of chitosan-based membrane alone or with BisBAL NPs showed similar results as elongation, suggesting that BisBAL NP addition did not affect membrane mechanical properties. Chitosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…14 We have previously reported the efficacy of bismuth lipophilic nanoparticles (BisBAL NPs) against several oral pathogens, including E. faecalis . 15 We have also demonstrated that the cement mineral trioxide aggregate (MTA) supplemented with BisBAL NPs acquired antimicrobial and antibiofilm activities against E. faecalis . 16 As a continuation of this work, here we report the antimicrobial potential of AH Plus BisBAL NPs against E. faecalis , both a commercial strain and clinical isolates from patients with endodontic infection.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…14 We have previously reported the efficacy of bismuth lipophilic nanoparticles (BisBAL NPs) against several oral pathogens, including E. faecalis . 15 We have also demonstrated that the cement mineral trioxide aggregate (MTA) supplemented with BisBAL NPs acquired antimicrobial and antibiofilm activities against E. faecalis . 16 As a continuation of this work, here we report the antimicrobial potential of AH Plus BisBAL NPs against E. faecalis , both a commercial strain and clinical isolates from patients with endodontic infection.…”
Section: Introductionmentioning
confidence: 93%
“…Bis-BAL NPs were synthesized and analyzed as previously reported. [15][16][17] Briefly, bismuth nitrate in propylene glycol (Bis) was mixed 2:1 with 2,3-dimercapto-1-propanol (BAL) to produce BisBAL nanostructures. The distributions of BisBAL NP size and shape were analyzed with scanning electron microscopy (SEM; FEI Tecnai G2 Twin, Hillsboro, OR; 160 kV accelerating voltage).…”
Section: Materials Development and Characterizationmentioning
confidence: 99%